RF and amplitude-based probe pressure correction for 3D ultrasound - Treece, Graham M.; Gee, Andrew H.; Prager, Richard W. (Ultrasound in medicine & biology, 2005)
Anatomical deformation caused by variable probe contact pressure is a significant problem in freehand 3D ultrasound, particularly for high resolution musculoskeletal and breast scans. We have previously published an amplitude-based algorithm for correcting such errors. In this paper, we compare this approach with a novel, elastography-inspired algorithm which works with the higher resolution radio-frequency (RF) signal. The results show that, although the RF-based algorithm is more precise in certain circumstances, both algorithms are able to compensate for probe pressure in 3D ultrasound data. Consequently, freehand 3D ultrasound users who do not have access to the RF signal are still in a position to perform effective probe pressure correction using the readily available video output, as long as this signal is not affected by significant amounts of frame averaging (persistence). (E-mail: gmt11@eng.cam.ac.uk)